Pharmacovigilance Knowledge among Patients at a Teaching Hospital in Lalitpur District, Nepal - Nisha Jha; Devendra S Rathore; P Ravi Shankar; Sudesh Gyawali (Journal of Clinical and Diagnostic Research, 2014)
Background: Consumer’s knowledge and perception towards adverse drug reactions (ADR) can play an important role in ensuring a healthy lifestyle and proper use of medicines. Aims: This study aimed to assess the knowledge and perception towards pharma covigilance in general and consumer pharmacovigilance in particular among out patients in a teaching hospital of Nepal. Settings and Design: A descriptive cross-sectional study using qualitative and quantitative methods was carried out from 1st May to 3 June 2013. Methods: Every fifth patient visiting the outpatient pharmacy was interviewed using a semi-structured questionnaire. Gender, age, educational qualification, profession and ethnicity were noted. Twenty-three patients were interviewed. Results: There were 10 males and 13 females. The age of the respondents ranged from 11 to 50 years with a mean age of 27.8 (SD = 5.61) years. Seven (30.43%) respondents were students studying in different levels. Thirteen (56.52%) participants were from the Newar community. Majority of the patients (86.95%) knew ADRs may be caused by the medicines they consume and 18 (78.26%) were of the opinion that ADRs should be reported to doctors and other health care professionals including pharmacists. Conclusion: Knowledge and perception were low in certain areas. There is a need for educational interventions for improving the awareness of patients and general public for ensuring medicine safety and promoting rational use of medicines.